Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1177/000348949910800501
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Idiopathic Sudden Sensorineural Hearing Loss: Antiviral Treatment of Experimental Herpes Simplex Virus Infection of the Inner Ear

Abstract: Experimental herpes simplex virus type 1 (HSV-1) labyrinthitis provides a model of idiopathic sudden sensorineural hearing loss (ISSHL). Corticosteroids improve the prognosis for hearing recovery in ISSHL, but the effects of acyclovir are unknown. To establish the therapeutic efficacy of acyclovir (Zovirax) and prednisolone in experimental HSV-1 viral labyrinthitis, we induced HSV-1 labyrinthitis in 12 guinea pigs. Three animals received no treatment, 3 received prednisolone, 3 received acyclovir, and 3 receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
10

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 16 publications
1
79
0
10
Order By: Relevance
“…Many authors report that spontaneous recovery happens in 45 to 60% of the patients 4,6,9,10 . In a more detailed fashion, it is estimated that about 25% of patients have total spontaneous recovery; 50%, partial and 25% present no recovery at all 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Many authors report that spontaneous recovery happens in 45 to 60% of the patients 4,6,9,10 . In a more detailed fashion, it is estimated that about 25% of patients have total spontaneous recovery; 50%, partial and 25% present no recovery at all 2 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Both adrenocorticoid and glucocorticoid receptors are found in the inner ear, though the precise mechanism of action is not known. 8 The main role of steroids is to protect the cochlea from inflammatory mediators released like TNA-a and NFK b. 9 Steroids increase the blood flow to the cochlea and regulate protein synthesis in cochlea.…”
Section: Discussion: Sudden Sensorineural Hearing Loss Is One Of the mentioning
confidence: 99%
“…5 Silverstein et al quoted that intra tympanic steroids are safe and do not produce histological changes in the cochlea. 8 The main clinical presentation is sudden hearing loss, which is also attributed to common ear fullness by the patients. The fullness in the ear can be due to wax impaction or congestion of Eustachian tube as in URTI.…”
Section: Discussion: Sudden Sensorineural Hearing Loss Is One Of the mentioning
confidence: 99%
“…2,4,8 The precise mechanism by which steroids may improve hearing remains unknown; both glucocorticoid and mineralocorticoid receptors may be found in the inner ear. 28 A few studies have shown that the main roles of steroids in the treatment of SHL are to protect the cochlea from the harmful effects of inflammatory mediators such as the tumor necrosis factor (TNF-a and NFK-b), which is elevated in infection and inflammation, 29 to increase cochlear blood flow 30 thereby avoiding cochlear ischemia, 31 to avoid noise-induced hearing loss, 32 and to regulate protein synthesis in the inner ear. 33 Studies have shown that the vascular stria, which regulates Na/K secretion for maintaining the endocochlear potential, is a site of injury in SHL.…”
Section: Discussionmentioning
confidence: 99%